Interdisciplinary Insights: Sociocognitive Approaches in Malay Applied Linguistics – A Bibliometric Perspective (LITPAM, 2024)
This study explores the evolving landscape of Malay Applied Linguistics (MAL) through the lens of sociocognitive approaches, employing a bibliometric perspective to unravel interdisciplinary insights. With a burgeoning interest in understanding the intricate interplay between language, society, and cognition, this study aims to map the trajectory of research trends within the field. By scrutinizing Google Scholar as a database, the analysis unveils the prevailing themes, influential contributors, and emerging concepts that shape the contemporary discourse in MAL in the range of the years 2018-2023 since it started to signify its trends. The bibliometric examination encompasses a diverse range of sources to provide a panoramic view of the field's intellectual landscape. Thus, this study employs advanced bibliometric techniques to identify patterns of knowledge across disciplines and the thematic evolution of research over time. Through this interdisciplinary approach, this study sheds light on the intersections of sociocognitive theories within the MAL domain, fostering a deeper understanding of the dynamic relationship between language use, cultural context, and cognitive processes.